Diagnostic utility of onychoscopy: Review of literature - Chander Grover; Deepak Jakhar (Wolters Kluwer Medknow Publications, 2017)
Onychoscopy is being increasingly used as a diagnostic modality for various nail diseases. Initial research had focused mainly on nail pigmentation and nailfold capillaroscopy; however, it is now being evaluated in various infectious and inflammatory nail disorders as well. The present review aims to summarize current knowledge about onychoscopic diagnostic criteria in nail diseases. The best level of evidence attached to each indication is mentioned to answer the pertinent question: How much can we rely on onychoscopy in confirming diagnosis of nail disease?